Comparing video and poster based education for improving 6-17 months children feeding practices: a cluster randomized trial in rural Benin: Video versus Poster in nutritional education - Bodjrènou, Fifali Sam Ulrich; Amoussa Hounkpatin, Waliou; Mitchodigni, Irène; Salako, Valère; Glèlè Kakaï, Romain; Dadélé, Yzé; Ntandou-Bouzitou, Gervais D.; Schneider, Lauriina; Mutanen, Marja; Savy, Mathilde; Kennedy, Gina; Hounhouigan, Joseph D.; et al. (Mattioli 1885, 2020)
Objective: This study aimed to assess whether short nutrition educational videos were more effective to improve child feeding practices compared to posters in a highly food insecure rural area in Southern Benin. Materials and Methods: A two-arm cluster-randomized trial was implemented in two districts of the Mono region, Benin. Over a 6 months period, eight villages received nutrition education sessions using either short videos (n=4 villages) or posters and flyers (n=4 villages). Dietary practices were collected among 6-17 months children (n=155) before and at the end of the nutrition education program using a qualitative 24 hours recall. UNICEF/WHO indicators for dietary diversification and meal frequency assessing were derived for each child. The videos versus posters effect was assessed by the difference-in-differences (DID) estimator using generalized estimated equations (GEE). Results: Overall, respectively 49% and 72% of children had achieved Minimum Dietary Diversity (MDD) and Minimum Meal Frequency (MMF) at baseline. Results from DID analysis showed that videos did not have significant advantage in terms of improving children feeding practices compared to posters neither for dietary diversity (DID = -0,036; p-value=0,651) nor for meal frequency (DID = -0,048; p-value=0,574). However, others factors namely children age, mother age and districts, had significant influence on these feeding practices. Conclusions: The nutrition education program using posters and videos performed the same in improving complementary feeding practices. The conditions of the utilisation of videos might be improved and other factors determining children feeding practices taken into account to allow mothers and other participants to benefit from nutrition sessions.